Competência leitora, música e metáfora conceptual: uma proposta a partir das canções de Luiz Gonzaga - Rodrigues, Fernanda (2021)
In a sociocognitive perspective our thoughts and actions are guided by metaphorical structures that are updated in the dynamics of socio-cultural relations and, because of such dynamics, they reflect the set of values circumscribed to a specific group. With this conception in mind, and considering the role of the school in the integral education of the student who has a special place in reading, this thesis aims to stimulate the development of reading competence for students in the 7th grade of the elementary school Colégio Estadual João Batista Nascimento, located in Nossa Senhora do Socorro, Sergipe, Brazil, through the analysis of conceptual metaphors present in the songs of Luiz Gonzaga. In order to deal with this proposal, a didactic sequence made of five modules is validated, with emphasis on the identification of metaphor and / or metaphorical expressions and the recognition of the effects of meanings that they update in the songs to be studied, with the purpose of improving the reading competence of student. The thesis has as a final product a workbook that will serve as a model so that Portuguese Language teachers can develop it in their classes. The workbook, entitled “Discovering the world of reading through the conceptual metaphor and songs of Luiz Gonzaga”, is based on the studies of Dolz et al (2004), who understand the didactic sequence as a promising tool for the development of learning, and is divided into five stages: i) Knowing the song lyrics; ii) Meeting Luiz Gonzaga, the King of Baião; iii) Discovering the world of reading and conceptual metaphor; iv) Game - Unraveling metaphors and v) Publicizing the work. From a theoretical point of view, these authors will be used: Lakoff and Johnson (1980), for whom the metaphor is a cognitive-social phenomenon; Sardinha (2007) for whom language is essentially metaphorical; Chiavegatto (2002), who highlights the sociocognitive motivations of Grammar; Marcuschi (2008), who points out that textual genres are part of our daily life; Koch and Elias (2015), who deal with conceptions of reading; Leffa (1996), for whom reading is a complex system; and Kleiman (2016) who understands the importance of training a critical reader.